2004
DOI: 10.1016/j.csr.2004.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial distribution of dissolved oxygen in the Pearl River Estuary and adjacent coastal waters

Abstract: The Pearl River is one of the large rivers in the world and it discharges to the northern part of the South China Sea. There has been a concern about the deterioration of dissolved oxygen conditions in the Pearl River estuary and adjacent coastal waters. In this study, historical data on dissolved oxygen (DO) from 1980, recent data from a summer cruise in 1999, and a 10-year time series in DO for 1990-2000 were used to examine spatial and temporal distribution of DO in the Pearl River estuary and adjacent coas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(116 citation statements)
references
References 43 publications
5
108
0
3
Order By: Relevance
“…Hypoxia that develops in coastal areas off the river mouths, notably the Mississippi River, Changjiang (Yangtze River), Pearl River (Zhujiang), Danube River, and Susquehanna River (Zaitsev, 1992;Turner and Rabalais, 1994;Li et al, 2002;Rabalais et al, 2002;Yin et al, 2004;Hagy et al, 2004;Black Sea Commission, 2008), usually has been related to anthropogenic activities in the catchment areas on land. In particular, changes in land-use and agriculture (e.g.…”
Section: Hypoxia Off River Mouths and In Estuariesmentioning
confidence: 99%
“…Hypoxia that develops in coastal areas off the river mouths, notably the Mississippi River, Changjiang (Yangtze River), Pearl River (Zhujiang), Danube River, and Susquehanna River (Zaitsev, 1992;Turner and Rabalais, 1994;Li et al, 2002;Rabalais et al, 2002;Yin et al, 2004;Hagy et al, 2004;Black Sea Commission, 2008), usually has been related to anthropogenic activities in the catchment areas on land. In particular, changes in land-use and agriculture (e.g.…”
Section: Hypoxia Off River Mouths and In Estuariesmentioning
confidence: 99%
“…the Pearl River discharge, the oceanic waters from the South China Sea and the coastal waters from the South China Coastal Current [24]. The resultant nutrient-enriched waters provide large biol ogical productivity and sustain the most important commercial fisheries [25,26].…”
Section: Study Areamentioning
confidence: 99%
“…Coupled with the monsoonal influence, the seasonal freshwater discharge from the Pearl River further complicates the hydrodynamics and biochemical processes. Previous studies suggested that the anthropogenic inputs of nutrients and organic matter in the Pearl River estuary have led to a decrease in oxygen and an increase in CO 2 , especially in the upper estuary (Yin et al, 2004;Cai et al, 2004;Dai et al, 2006). Zhai et al (2005a) have reported that aerobic respiration is the most important process in maintaining a high pCO 2 level (>3000 µatm) in the upstream section of the Pearl River estuary.…”
mentioning
confidence: 99%